Laser Surface Modification of H13 Die Steel using Different Laser Spot Sizes - S. N., Aqida; Naher, Sumsun; Brabazon, Dermot (American Institute of Physics, 2011)
This paper presents a laser surface modification process of AISI H13 tool steel using three sizes of laser spot with an aim to achieve reduced grain size and surface roughness. A Rofin DC'015 diffusion'cooled CO2 slab laser was used to process AISI H13 tool steel samples. Samples of 10 mm diameter were sectioned to 100 mm length in order to process a predefined circumferential area. The parameters selected for examination were laser peak power, overlap percentage and pulse repetition frequency (PRF). Metallographic study and image analysis were done to measure the grain size and the modified surface roughness was measured using two'dimensional surface profilometer. From metallographic study, the smallest grain sizes measured by laser modified surface were between 0.51 3m and 2.54 3m. The minimum surface roughness, Ra, recorded was 3.0 3m. This surface roughness of the modified die steel is similar to the surface quality of cast products. The grain size correlation with hardness followed the findings correlate with Hall'Petch relationship. The potential found for increase in surface hardness represents an important method to sustain tooling life.